Saving whom?: The ethical challenges of harvesting tissue from savior siblings - Rubeis, Giovanni; Steger, Florian (European journal of haematology, 2019)
Purpose of the study: To discuss the ethical challenges for the therapeutic team when dealing with a young savior sibling as a potential tissue donor. Basic procedures: Savior siblings are children that are created to serve a sibling as a donor of umbilical cord blood, bone marrow, or peripheral blood from which hematopoietic stem cells are derived. These cells are used for hematopoietic stem cell therapy, which is the only curative treatment for certain hemoglobinopathies. We used a case including a 19‐year‐old thalassemia patient and his two and a half year old sister from our practice as ethics consultants. Our methodological basis is the principlism approach by Beauchamp and Childress, consisting of four principles: autonomy, non‐maleficence, beneficence, and justice. Main findings: We found that the main conflict arises between the autonomy of the savior sibling as well as the non‐maleficence regarding her and the beneficence of the thalassemia patient. Principal conclusions: Decision‐making is complex when decisions within the family are concerned, especially when non‐competent young children are involved. The therapeutic team does not only have to recognize the principal vulnerability of children but also the different scales of vulnerability depending on their age.
Gesehen am 12.12.2019